2011
DOI: 10.4261/1305-3825.dir.4933-11.1
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasonography guided percutaneous thrombin injection of postcatheterization pseudoaneurysms

Abstract: Femoral artery pseudoaneurysms are among the most frequent complications of angiography. Factors that predispose a patient to pseudoaneurysm formation are inadequate compression, simultaneous artery and vein catheterization, hypertension, obesity, hemodialysis, heavily calcified arteries, and low femoral puncture. The risk of pseudoaneurysm formation also increases when large-bore sheaths, postprocedural anticoagulation therapy, and/or antiplatelet therapy are used as interventions (1, 2). The incidence of fem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
22
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(24 citation statements)
references
References 13 publications
1
22
0
1
Order By: Relevance
“…The complication rate, considered separately, was 3.0%. These results are concordant with those in prior studies, which suggest that ultrasound‐guided thrombin injection is a relatively effective and safe treatment . It is noteworthy that no immediate complications were identified in the 32 patients who were excluded from this study for loss to follow‐up.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The complication rate, considered separately, was 3.0%. These results are concordant with those in prior studies, which suggest that ultrasound‐guided thrombin injection is a relatively effective and safe treatment . It is noteworthy that no immediate complications were identified in the 32 patients who were excluded from this study for loss to follow‐up.…”
Section: Discussionsupporting
confidence: 91%
“…Although a number of additional studies have demonstrated ultrasound-guided thrombin injection to be both safe and efficacious, [7][8][9][10][11][12][13][14][15][16][17][18][19] most have been conducted with relatively small sample sizes, and few have focused on the need for follow-up imaging or described the factors associated with pseudoaneurysm recurrence. The purpose of this study was to review cases of ultrasoundguided thrombin injection of pseudoaneurysms performed over a 10-year period to determine the procedural success rate, the procedural complication rate, the rate of pseudoaneurysm recurrence, and the factors associated with failure of complete and sustained pseudoaneurysm thrombosis to be able to recommend appropriate follow-up imaging.…”
mentioning
confidence: 99%
“…Thromboembolic events arise from thrombin flow beyond site of the aneurysm into the arterial system 3. Some studies have shown this method is more successful in acute pseudoaneurysms within the first few weeks of their development 9. Many authors also consider this method unsuitable for treating aneurysms with a wide neck as they have a slightly higher risk of embolisation.…”
Section: Discussionmentioning
confidence: 99%
“…However, the presence of infection is not an absolute contraindication to minimally invasive techniques, and management should be tailored to the individual case. Careful evaluation of the imaging studies, particularly CT angiography, is essential to determine the proper treatment and hence reduce the risk of complications in order to achieve the best possible results 1–3 9Learning points

Aneurysms can masquerade as a mass or an abscess, so careful evaluation of imaging studies is essential to rule out a vascular origin prior to lesion intervention.

Vascular lesions may be discovered incidentally during routine investigation of non-specific symptoms such as pain in a particular location, and so radiologists must be familiar with their imaging findings, particularly on MRI.

Contrast-enhanced CT is the gold standard for the investigation of lesions suspected of having a vascular origin.

Although minimally invasive procedures, such as percutaneous thrombin injection, are considered to be safe in comparison to open surgery, they may still result in serious complications, so careful evaluation is required to determine optimal treatment.

…”
Section: Discussionmentioning
confidence: 99%
“…This had a high success rate, but with the possibility of complications at the entry puncture site, usually a femoral vessel. Percutaneous injection of thrombin for IEA pseudo-aneurysm was first described in 20026 and this method has been established in treating pseudo-aneurysms at other sites, with a success rate of around 91–100% 7. The simplicity of percutaneous injection with no significant complications, except for the theoretical risk of thrombin migration into the patent artery, makes this procedure the first choice.…”
Section: Discussionmentioning
confidence: 99%